Formant Trajectories in CV Clusters for German Stops - Kuczmarski, Tomasz (Investigationes Linguisticae, 2009)
This paper presents an attempt to demonstrate the nonlinear progress of vowel formants in German CV clusters with stop sounds and identify it as a significant acoustic property characterizing the place of articulation of the stop consonant.